Local Angler Knowledge Reveals Declines in Fishing Quality for Black Bass in Lakes of Eastern Ontario - Joel Zhang; David P. Philipp; Julie E. Claussen; Cory D. Suski; Vivian M. Nguyen; Nathan Young; Luc LaRochelle; Justin W. Lombardo; Steven J. Cooke (Fisheries Management and Ecology, 2026)
Local ecological knowledge can be useful to assess data‐limited fisheries such as the Ontario Black Bass ( Micropterus spp.) recreational fishery. We surveyed local anglers using the Life History Calendar approach to determine if there were perceived changes in fishing quality for Black Bass in eastern Ontario across different time periods. For both species (Largemouth Bass and Smallmouth Bass), respondents noted declines in numbers and body sizes of their catch across most of the time periods (1975–2025) with sharp declines beginning in 2005. The reported declines were notably consistent across the waterbodies studied and did not differ across different user types (e.g., tournament anglers vs. other anglers). The results of this study show that anglers overwhelmingly perceive that the quality of bass fishing in eastern Ontario has deteriorated over the past few decades, highlighting the (1) utility of using local angler knowledge to complement traditional stock assessment methods and (2) the need to consider alternative monitoring and management strategies to reverse those declines.